2019
DOI: 10.1111/bjso.12359
|View full text |Cite
|
Sign up to set email alerts
|

Leavers and Remainers after the Brexit referendum: More united than divided after all?

Abstract: Since the British ‘Brexit referendum’ in 2016, tensions between ‘leave’ and ‘remain’ voters have been growing. Using a novel analytical approach based on the full distribution of responses rather than their arithmetic means, Study 1 (N = 1,506) showed on average 90% of overlap among Leavers and Remainers across a range of important variables. Even on the variables that are commonly used to illustrate how Leavers and Remainers differ (e.g., prejudice against immigrants), the amount of overlap was larger than 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 65 publications
(106 reference statements)
2
8
0
1
Order By: Relevance
“…Study 2 was part of a larger survey in which additional societal and environmental concerns, civic engagement, and political attitudes were measured. These data were used in another manuscript to compare those who voted to leave Europe with those who voted to remain during the EU Referendum in June 2016 (Hanel & Wolf, 2018). In this other manuscript, no comparisons between own and perceived values are made.…”
Section: Methodsmentioning
confidence: 99%
“…Study 2 was part of a larger survey in which additional societal and environmental concerns, civic engagement, and political attitudes were measured. These data were used in another manuscript to compare those who voted to leave Europe with those who voted to remain during the EU Referendum in June 2016 (Hanel & Wolf, 2018). In this other manuscript, no comparisons between own and perceived values are made.…”
Section: Methodsmentioning
confidence: 99%
“…However, some reconciliation between voters could happen. Hanel and Wolf (2019) demonstrated that Leave voters were more against immigrants, but the similarity of views between them and Remainers on migration was still 51%. My findings added that some Leavers would support high migration levels from certain countries.…”
Section: Discussionmentioning
confidence: 99%
“…The ESS employs strict probability samples of the population aged 15 and over. We exclude those countries that are not European Union members, including the United Kingdom, the respondents from which were not asked about how they would vote in such a referendum and instead asked about how they voted in the 2016 referendum, subjecting responses to different, unique dynamics that have been studied elsewhere, including in terms of the effects of Schwartz’s values (Dennison et al, 2020; Hanel & Wolf, 2020). Thus, this variable may not be comparable in the UK with the one measured in the other countries.…”
Section: Data Measures and Methodsmentioning
confidence: 99%